2018
DOI: 10.1108/jopp-11-2018-021
|View full text |Cite
|
Sign up to set email alerts
|

Early contractor involvement approaches in public project procurement

Abstract: Early contractor involvement (ECI) faces many barriers when it is implemented in public procurement, given that it is different from traditional business practices. Primarily, public owners face a major challenge, as they should treat all bidders equally. The purpose of this paper is to explore suitable ECI approaches that public owners could use. In addition to a literature and document study, fourteen semi-structured in-depth interviews with key personnel from eleven cases selected from Norwegian public brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Thus, a major theme in construction procurement research deals with possibilities to enhance collaboration in this traditionally adversarial and fragmented industry. There is increased use in many countries of flexible, integrated models that involve contractors earlier in the process (Lahdenper€ a 2012; Wondimu et al 2018). Such strategies often comprise procurement criteria to select contractors based on other dimensions than price, collaborative project management measures and payment systems designed to share risks (Eriksson 2015).…”
Section: Contracts and Incentives In Constructionmentioning
confidence: 99%
“…Thus, a major theme in construction procurement research deals with possibilities to enhance collaboration in this traditionally adversarial and fragmented industry. There is increased use in many countries of flexible, integrated models that involve contractors earlier in the process (Lahdenper€ a 2012; Wondimu et al 2018). Such strategies often comprise procurement criteria to select contractors based on other dimensions than price, collaborative project management measures and payment systems designed to share risks (Eriksson 2015).…”
Section: Contracts and Incentives In Constructionmentioning
confidence: 99%
“…Some research has shown negative impacts from inattention to the planning phase, and especially a lack of market studies and research (Gutiérrez Rodríguez 2020). In the development of specifications, improved understanding of requirements can be of great benefit to the success of a project, as demonstrated by Wondimu et al (2018). Some recommend more contractor involvement in early project phases, to enhance specification, improve project timelines, and provide for cost-efficiency (Love et al 2014).…”
Section: Problems Associated With Incomplete or Insufficient Planningmentioning
confidence: 99%
“…It is recognized that the ability of the parties to influence project outcomes, including reduction of cost, creation of additional value, improvement of performance and flexibility to incorporate changes is much higher in the conceptual and design stages of the project (Mosey, 2009). ECI can be achieved by several approaches, and one of the approaches is BVP (Wondimu et al 2018b).…”
Section: Theoretical Background Early Contractor Involvementmentioning
confidence: 99%
“…Partnering is characterized by trust, open and effective communication, common goals and early involvement of suppliers (Hosseini et al 2018). There are several approaches for implementing ECI in the public sector and BVP is one of them (Wondimu et al 2018b). BVP seeks to facilitate an efficient procurement where the vendor delivers according to the client's project ambitions, reduces the client's risk and minimizes the stakeholders' use of resources (van de Rijt et al 2016).…”
Section: Introductionmentioning
confidence: 99%